KARAKTERISTIK HABITAT DAN POTENSI KEPITING BAKAU (Scylla serrata, S.transquaberica, and S.olivacea) DI HUTAN MANGROVE CIBAKO, SANCANG, KABUPATEN GARUT JAWA BARAT - Irvan Avianto; Sulistiono Sulistiono; Isdrajad Setyobudiandi (AQUASAINS, 2013)
The research aimed to collectdata and information about the habitatcaracteristics and mud crabs potency in Cibakomangrove forest. Sampling was conductedthrough line plot transect survey.Parameters examined physical-chemical characteristic,mangrove vegetation, mud crabspopulation and size distribution. Habitatcharacteristics were collected cluster analisys.The result showed that some parametersof habitat were resemblance wherestations 1 and 2 were Groups A, stations3 and 4 were groups B , and station 5 and6 were groups C. The mud crabs populations,size distribution, and habitat groupswere analyzed correspondence analysis.S.serrata dominate in zone A in dark totaled67 ind. individual existence S.serrataallegedly tolerant of high salinity > 28 0/00and macrozoobenthos abundance of mangrovecrabs as a food source. S.tanquabericadominate in zone B in the dark was 70 ind.The presence of individual species in zoneB allegedly tolerant of salinity 24 -> 280/00, natural food abundance and habitatsuitability as a mud substrate. S.olivaceadominate in the zone C in the dark totaled38. The presence of individual speciesin zone C allegedly due to low salinity tolerant in the range of 21-22 0/00 and canlive on clay substrate.